Optimizing the Interface Solvation Structure Enables Uniform Zinc Deposition for Zinc Metal Batteries - Chang Liu; Tiantian Lu; Ziyang Liang; Xiang Bai; Jiahui Zhang; Xinyue Chang; Lixiang Guan; Lifeng Hou; Yinghui Wei; Qian Wang; Qi Liu (Energy Material Advances)
Rechargeable aqueous Zn metal battery demonstrates great potential in grid-type energy storage systems due to its low cost, high safety, and environmental friendliness. However, its practical application is still restricted by Zn dendrite growth and side reactions from the Zn metal anode. Here, we propose a uniform Zn deposition mechanism by optimizing the interface solvation structure using trace isonicotinamide (ISO; only 0.77$/g) as the electrolyte additive. Unlike previously reported acidic additives, which will reduce the electrolyte pH and potentially exacerbate corrosion, ISO molecules do not experience this anxiety. At the same time, ISO can be adsorbed on the surface of Zn electrodes and participate in the dissolution of the structure, adjusting the coordination microenvironment of Zn2+ at the interface and removing the active H2O molecules, thereby improving the interface stability of the Zn metal anode and reducing side reactions substantially. As a result, the Zn | Cu half cells can stably run over 900 cycles with a high coulombic efficiency of >99.5% at a current density of 1.0 mA/cm2. Perhaps more significantly, the symmetric cells witness an extremely long cycle life (>8,700 h, almost 1 year) even at a low current density of 0.2 mA/cm2. Lastly, the full cells with V2O5 cathode show better capacity retention after 1,000 cycles. This work provides a new pathway to developing advanced electrolyte additives for high-performance aqueous Zn metal batteries.